2021
DOI: 10.1093/jee/toab113
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics and Reproductive Developmental Analysis ofHelicoverpa armigera(Lepidoptera: Noctuidae) Trapped Using Food Attractants in the Field

Abstract: Monitoring adult populations of Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae), a major agricultural pest, provides data useful for its control. Food attractants, considered as adult insect behavior regulators based on the preference of an herbivorous pest for food sources or their volatiles, also have great potential for monitoring populations. To study the feasibility of monitoring the population dynamics and reproductive development of H. armigera in the field using food attractants, we quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 15 publications
4
15
0
Order By: Relevance
“…Our field trapping test results showed that in the toxicant‐infused bait treatment fields and control treatment fields, male H. armigera moths attracted by the bio‐bait Bioattract®‐Heli were ranged from 2 to 10 days old. The length of the testes of male H. armigera moths attracted in the control and toxicant‐infused bait treatment fields decreased significantly with the stage of investigation, whereas the age of male moths increased significantly with the stage of investigation, which was consistent with the results reported in the literature 36,47 . These results indicate that bio‐bait Bioattract®‐Heli has similar attractive activity for both young and old males, and using bio‐bait Bioattract®‐Heli as the ‘attract‐and‐kill’ attractant can significantly reduce the population of H. armigera male moths in the field.…”
Section: Disscussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our field trapping test results showed that in the toxicant‐infused bait treatment fields and control treatment fields, male H. armigera moths attracted by the bio‐bait Bioattract®‐Heli were ranged from 2 to 10 days old. The length of the testes of male H. armigera moths attracted in the control and toxicant‐infused bait treatment fields decreased significantly with the stage of investigation, whereas the age of male moths increased significantly with the stage of investigation, which was consistent with the results reported in the literature 36,47 . These results indicate that bio‐bait Bioattract®‐Heli has similar attractive activity for both young and old males, and using bio‐bait Bioattract®‐Heli as the ‘attract‐and‐kill’ attractant can significantly reduce the population of H. armigera male moths in the field.…”
Section: Disscussionsupporting
confidence: 89%
“…Our research results show that toxicant‐infused bait can strongly attract and kill H. armigera adults, similar to the results found in studies of fall armyworms, sugar beet moths and other pest moths 29,47,48 . The number of male and female H. armigera adults attracted and killed by strip application of toxicant‐infused bait ranged from 1 to 37 and 4 to 36 per strip, respectively, of which female moths accounted for 53%, consistent with the results in cotton, maize, soybean and peanut fields by He et al 36 …”
Section: Disscussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In particular, monitoring the population dynamics is essential for timely and effective pest management. 5 At present, the methods for the detection of H. armigera as well as other pests include crop investigation, field sampling, and sexual trap, 6 which are inconvenient and laborintensive. A method with low cost, quick response, high accuracy, and real-time monitoring capability is highly desirable for the efficient control of pests such as H. armigera.…”
mentioning
confidence: 99%
“…Early detection and monitoring of pests are important to control the infestation. In particular, monitoring the population dynamics is essential for timely and effective pest management . At present, the methods for the detection of H.…”
mentioning
confidence: 99%